The Policy and Service Creation – Necessary Shifts for Working With NEETs From the Perspective of Young People and Professionals - Paabort, Heidi; Beilmann, Mai (Calitatea Vieții, 2025)
The European Commission's Youth Guarantee initiative has brought renewed attention to the increasingly complex support needs of young people not in education, employment, or training (NEETs), particularly as they navigate key transitional phases in their lives. This study contributes to the understanding and evaluation of policies aimed at this demographic, as well as shifts in the broader policy landscape intended to enhance the effectiveness of interventions and ensure that support aligns more closely with young people’s perceived needs. Drawing on semi-structured interviews with youth in NEET situations and professionals working with them in Estonia, the study underscores the necessity of adopting more community-based and participatory approaches to support interventions. Incorporating more inclusive, empowering, and confidence-building principles−such as the need for a minimal information flow requirement, situation-based communication, meaning-based change management, co-creation and reciprocal partnership, one-shop change management, a need-based rebalancing, and long-term legitimate expectation can play a crucial role in preventing the marginalization and social exclusion of target groups. These principles are essential for improving access to information, education, support services, and labour market opportunities. Realizing such an approach requires national-level strategic agreements that shift the focus of Member States from isolated actions to comprehensive implementation strategies, paving the way for the co-creation of an integrated, cross-sectoral support ecosystem. The article concludes with practical policy recommendations that are scalable at the European level.